The Implementation of Project Based Learning Model in CAD/CAM Instruction to Improve Learning Outcomes of Mechanical Engineering Students - Feby Indayani; Mulyana; Zumrotul Avifa Kasjib; Nirmala Dewi (Universitas Muhammadiyah Palu, 2025)
This study aims to analyze the effectiveness of implementing the Project Based Learning (PjBL) model in the CAD/CAM course to improve the learning outcomes of Mechanical Engineering students at Universitas Tomakaka. Using a quasi-experimental method with a pretest-posttest control group design, the study involved 60 fourth-semester students divided equally into an experimental group taught with PjBL and a control group taught using conventional methods. Data were collected through cognitive tests, project assessments, and affective rubrics, then analyzed using normality and homogeneity tests, independent t-tests, and N-Gain scores.The findings showed that the experimental group experienced significant improvement in cognitive learning outcomes, with higher posttest scores and moderate to high N-Gain values, compared to the control group, which demonstrated only low improvement. Psychomotor outcomes also revealed a strong positive effect, with the PjBL group outperforming the control group in 3D modeling accuracy, design quality, and software utilization. Furthermore, affective outcomes highlighted that the experimental group exhibited greater teamwork, communication, and participation, supported by significant statistical differences.These results confirm that PjBL is an effective learning model that enhances not only cognitive and technical competencies but also essential soft skills required by the engineering profession. The integration of PjBL in CAD/CAM courses provides a holistic learning experience that prepares students to face the challenges of Industry 4.0. This study recommends broader implementation of PjBL in technical education, supported by adequate facilities and collaboration with industry to ensure the relevance and sustainability of project-based curricula.